여성하지정맥류에서 에스트로겐 수용체의 과다발현 - 한상문(Sang Moon Han); 김원우(Won Woo Kim); 박장상(Jang Sang Park) (Annals of surgical treatment and research, 2006)
Purpose: The high frequency of varicose veins in female suggests the involvement of female sex hormone in pathophysiology of varicose vein. We investigated the presence of estrogen receptor in the wall of normal and varicose veins, and compared their expression between male and female. Methods: Twenty normal veins were obtained from patient undergoing peripheral artery bypass surgery. Forty varicose segment and non-varicose segment of varicose veins in same patients were obtained from patient during operation. Using immunohistochemistry, we measured estrogen receptor expression rate and compared the estrogen receptor expression of varicose vein with that of normal vein. Results: There is no difference on estrogen receptor expression between normal vein and varicose vein. The positive rate of estrogen receptor expression was higher in varicose segment of varicose vein than in non-varicose segment of varicose vein (P=0.039). In varicose segments in female, estrogen receptor positive rate was higher than non-varicose segment (P=0.022), and than normal vein (P=0.017). The estrogen receptor positive rate of varicose segment in varicose vein was higher in female than male (P=0.008). But there is no statistical significance for the estrogen receptor positive rate of non-varicose segment in varicose vein between male and female. Conclusion: The gender difference may be related to hormonal action. Also, these finding suggested the involvement of female sex hormone in varicosity and provides a basis for the finding of causes of primary varicose veins. (J Korean Surg Soc 2006;71:61-64) KCI Citation Count: 1